2005
DOI: 10.1128/aem.71.10.5850-5857.2005
|View full text |Cite
|
Sign up to set email alerts
|

Photoheterotrophic Metabolism of Acrylamide by a Newly Isolated Strain of Rhodopseudomonas palustris

Abstract: Acrylamide, a neurotoxin and suspected carcinogen, is produced by industrial processes and during the heating of foods. In this study, the microbial diversity of acrylamide metabolism has been expanded through the isolation and characterization of a new strain of Rhodopseudomonas palustris capable of growth with acrylamide under photoheterotrophic conditions. The newly isolated strain grew rapidly with acrylamide under photoheterotrophic conditions (doubling time of 10 to 12 h) but poorly under anaerobic dark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 29 publications
4
56
0
Order By: Relevance
“…For AMD degrading-bacteria, AA is probably reduced to generate energy for bacterial growth but the catabolic pathway is not clear. Wampler and Ensign (2005) suggested that AA is degraded to β-hydropropionate via hydroxylation reaction, then oxidized to CO 2 or reduced to propionic acid. Recently, Charoenpanich and Tani (2014) have studied the response of an acrylamidedegrader Enterococcus aerogenes to AMD using proteome analysis.…”
Section: Metabolism Of Acrylamide and Enzymes Involved In Bio-degradamentioning
confidence: 99%
“…For AMD degrading-bacteria, AA is probably reduced to generate energy for bacterial growth but the catabolic pathway is not clear. Wampler and Ensign (2005) suggested that AA is degraded to β-hydropropionate via hydroxylation reaction, then oxidized to CO 2 or reduced to propionic acid. Recently, Charoenpanich and Tani (2014) have studied the response of an acrylamidedegrader Enterococcus aerogenes to AMD using proteome analysis.…”
Section: Metabolism Of Acrylamide and Enzymes Involved In Bio-degradamentioning
confidence: 99%
“…In this last respect, bacteria capable of utilizing acrylamide in vitro as the sole carbon and nitrogen source have been isolated (Wampler and Ensign, 2005). Furthermore, recent studies have shown that some lactic acid bacteria such as Lactobacillus reuteri NRRL 14171 and Lactobacillus casei Shirota, possess the capability to remove acrylamide in aqueous solution by physically binding of the toxin to the bacterial cell wall (Serrano-Niño et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1982, microbial degradation of acrylamide has been explored extensively with a diversity of isolates (Table 1), mainly Bacillus, Pseudomonas and Rhodococcus [3,[46][47][48][49][50][51][52][53][54][55]. Further, numerous other microorganisms including the representatives of Arthrobacter, Xanthomonas, Rhodopseudomonas, Rastonia, Geobacillus, and a newly family of Enterobacteriaceae [49,[56][57][58][59][60][61][62]. Aspergillus oryzae, a filamentous fungal has also been documented as an acrylamide degrader [63].…”
Section: Microbial Degradation Of Acrylamidementioning
confidence: 99%
“…Recently a new strain of Rhodopseudomonas palustris was found capable of using acrylamide under photoheterotrophic conditions but grew poorly under anaerobic dark or aerobic conditions. A study of acrylamide metabolism by nuclear magnetic resonance showed the rapid deamidation of acrylamide to acrylate and further to propionate [57]. More recently, the denitrifying bacterium, Ralstonia eutropha TDM-3 isolated from the wastewater treatment system associated with the manufacture of polyacrylonitrile fiber consumed acrylamide to concentration of 1446 mg/l, above which it was toxic [58].…”
Section: Microbial Degradation Of Acrylamidementioning
confidence: 99%